Determinants of Financial Performance Using Islamic Social Responsibility as an Intervening Variable in Sharia Commercial Banks in Indonesia - Simanungkalit, Gustin Tamara; Nurlaila, Nurlaila; Rahmani, Nur Ahmadi Bi (Universitas KH. Abdul Chalim Mojokerto, 2024)
Financial performance describes the company's financial condition in a certain period, both regarding raising funds and distributing funds, which is usually measured by capital adequacy, liquidity, and profitability indicators. This research examines the influence of financing-to-deposit ratio, Company Size, and Non-Performing Financing on Financial Performance with Islamic Social Responsibility as an intervening variable. This research uses secondary data from the 2019-2023 period at Sharia Commercial Banks. The sampling technique uses purposive sampling. The tool for processing the data uses SPSS 26.0. The research results show that the Financing to Deposit Ratio significantly affects Financial Performance. Company size has a significant effect on financial performance. and Non-Performing Financing does not have a significant effect on Financial Performance. Meanwhile, the Financing to Deposit ratio significantly affects Islamic Social Responsibility, Company Size significantly affects Islamic Social Responsibility and Non-Performing Financing has no significant effect on Islamic Social Responsibility. Furthermore, the financing-to-deposit ratio has a significant effect on Financial Performance through Islamic Social Responsibility. Islamic Social Responsibility can mediate the influence of Financing to Deposit Ratio on Financial Performance. Company Size has a significant effect on financial performance through Islamic Social Responsibility. Islamic Social Responsibility can mediate the influence of Company Size on Financial Performance, and Non-Performing Financing has no significant effect on Financial Performance through Islamic Social Responsibility. Islamic Social Responsibility cannot mediate the influence of Non-Performing Financing on Financial Performance. Meanwhile, Islamic Social Responsibility has a significant effect on Financial Performance.